Nutritional Status of Settler and Indigenous Women of Reproductive Age Group in Khagrachari District, Bangladesh - Haque, Md Monoarul; Akter, Jesmin; Ahmed, Kazi Rumana; Chowdhury, Hasina Akhter; Hossain, Sharmin; Tripura, Nantu Bikash (Journal of Enam Medical College, 2014)
Background: Reproductive health is closely related with nutritional status of a country. Women are regarded as the nerve centers of the families and society, maternal nutrition and health is considered as the most important regulator of human fetal growth. Objective: This study was conducted with a view to assess the nutritional status of settler and indigenous women of reproductive age group (15–49 years) in Khagrachari district. Materials and Methods: This cross sectional study was done in the purposively selected Panchari thana of Khagrachari district in Bangladesh from 01 May to 31 August 2013. A total of 200 reproductive aged women were interviewed. Among them 100 were indigenous and 100 were settlers. Their anthropometric measurements were taken and nutritional status was determined by body mass index (BMI) recommended by World Health Organization (WHO) for Asian people. Results: The mean age of the respondents was 29.8 ± 11.1 years and maximum were in the age group of 15–24 years. Among the indigenous subjects Chakma, Marma, Tripura and Boisnu were 20.5%, 20.5%, 6.5% and 2.5% respectively. Among 100 indigenous reproductive aged women 17 were underweight; but among settlers 19 were underweight. Forty nine settler women were normal and in case of indigenous women 46 were normal. But regarding overweight indigenous women went ahead than settler women and obesity was found equal in both groups. Mean difference of mid upper arm circumference (MUAC) was significantly different (p<0.005) between the groups. Conclusion: This study provided a vivid picture of the nutritional status of the settler and indigenous reproductive aged women. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19677 J Enam Med Col 2014; 4(2): 98-101